Identification of novel genes including NAV2 associated with isolated tall stature - Weiß, Birgit; Ott, Tim; Vick, Philipp; Lui, Julian C.; Röth, Ralph; Vogel, Sebastian; Waldmüller, Stephan; Hoffmann, Sandra; Baron, Jeffrey; Wit, Jan M.; Rappold, Gudrun (Frontiers in endocrinology, 2023)
Very tall people attract much attention and represent a clinically and genetically heterogenous group of individuals. Identifying the genetic etiology can provide important insights into the molecular mechanisms regulating linear growth. We studied a three-generation pedigree with five isolated (non-syndromic) tall members and one individual with normal stature by whole exome sequencing; the tallest man had a height of 211 cm. Six heterozygous gene variants predicted as damaging were shared among the four genetically related tall individuals and not present in a family member with normal height. To gain insight into the putative role of these candidate genes in bone growth, we assessed the transcriptome of murine growth plate by microarray and RNA Seq. Two (Ift140, Nav2) of the six genes were well-expressed in the growth plate. Nav2 (p-value 1.91E-62) as well as Ift140 (p-value of 2.98E-06) showed significant downregulation of gene expression between the proliferative and hypertrophic zone, suggesting that these genes may be involved in the regulation of chondrocyte proliferation and/or hypertrophic differentiation. IFT140, NAV2 and SCAF11 have also significantly associated with height in GWAS studies. Pathway and network analysis indicated functional connections between IFT140, NAV2 and SCAF11 and previously associated (tall) stature genes. Knockout of the all-trans retinoic acid responsive gene, neuron navigator 2 NAV2, in Xenopus supports its functional role as a growth promotor. Collectively, our data expand the spectrum of genes with a putative role in tall stature phenotypes and, among other genes, highlight NAV2 as an interesting gene to this phenotype.